ACADEMIC INFORMATION SYSTEM FOR NEW STUDENT ADMISSION USING STRUCTURED ANALYSIS AND DESIGN TECHNIQUE (SADT) METHOD AT PRIVATE ELEMENTARY SCHOOL PENGHARAPAN - Waruwu, Sokhizatulo; Elsera, Marina; Hadinata, Edrian (Cattleya Darmaya Fortuna, 2025)
New student admission is an important stage in the academic system in elementary schools that affects the effectiveness of administration and transparency of selection. However, in SD Swasta Pengharapan, the new student admission process is still carried out manually, which causes various problems such as inefficient data recording, the risk of losing documents, and delays in delivering information to prospective students and parents. Therefore, this study aims to design and build a web-based New Student Admission Academic Information System using the Structured Analysis and Design Technique (SADT) method to improve efficiency, accuracy, and transparency in managing new student admission data. The SADT method was chosen because of its systematic approach in analyzing and designing the system with clear and structured diagram modeling. This study began with the needs analysis stage, where observations and interviews were conducted with the school to understand the existing problems. Furthermore, the system design was carried out using context diagrams, data flow diagrams (DFDs), and entity-relationship diagrams (ERDs) to describe the data flow and relationships between entities in the system. The system implementation was carried out by building a web-based application that allows the registration process to be carried out online, automatic data verification, and more accurate and faster management of selection results. The results of this study indicate that the developed system is able to increase efficiency in the process of accepting new students, reduce the use of physical documents, and accelerate the delivery of information to prospective students and parents. With this system, the school can manage prospective student data in a more structured and easily accessible manner, thereby improving the quality of academic services at SD Swasta Pengharapan.